PENINGKATAN KEMAMPUAN MEMAHAMI ISI BACAAN MENGGUNAKAN METODE READ ALOUD BERBASIS VIDEO PADA SISWA KELAS II - Nunuy Nurkaeti (Journal of Professional Elementary Education, 2023)
This study aims to solve problems regarding the low reading ability of students in understanding reading content in class II of SDN Gandaria Utara 01 through learning using the video-based read aloud method. This research used a quantitative research experimental method using only one research sample, namely the experimental group (pretest and posttest one group design). The sample for this research was Grade II students at SDN Gandaria Utara 01. Based on the results of the study, there was an increase in reading skills in terms of fluency and the ability to understand the contents of the reading. The increase in reading fluency was 14.66 from the initial average of 71.86 and the ability to understand the contents of reading was 28.93 from the initial average of 62.19. This shows an increase in students' reading skills, especially in understanding the contents of the reading. The use of the video-based read aloud method also increased student responses to learning to read by as much as 31.75%.